Learning environment variables and the efficacy of student learning in secondary school in Abak local government, Akwa Ibom State - Sakirudeen, Abisola Oladeni (Revija za elementarno izobraževanje, 2020)
Four research questions and four null hypotheses were formulated to guide the study. A simple random sampling technique was used in selecting 34 respondents from each 6 schools, with a sample size of 204 was selected from the population of 1,518. The instrument titled LEVSLEQ was used to elicit response from the respondent. The reliability of the research instrument yielded a co-efficient of 0.82. The data was analyzed using dependent t-test and was tested at .05 level of significance. The findings indicated that environmental variable studied influence students' learning effectiveness.
Keywords: environment; learning; learning effectiveness; okolje; spremenljivke; students; učenci; učenje; učna učinkovitost; variables